First report of complete albinism in Mazama americana (Erxleben, 1777) in the Biological Reserve of Tapirapé, Oriental Amazon, Brazil - Raquel Ribeiro; Diogenes Henrique de Siqueira-Silva (Acta Scientiarum: Biological Sciences, 2020)
Albinism is a genetic condition that results in total hypopigmentation of the eyes, fur, skin, hair, scales, and feathers of an organism. Albinism might result in a selective disadvantage for affected animals. Cases of albinism have been previously recorded in Neotropical vertebrates, such as reptiles, mammals, birds, and fish. However, observing albinism in a wild population is still considered to be a rare event. This paper reports a unique case of complete albinism in a red-brocket deer (Mazama americana) living in the Brazilian Amazon rainforest. The individual was observed within the Biological Reserve of Pará State, one of the most deforested regions of the Brazilian Amazon. The survival of the albino red-brocket deer in the wild can be related to mechanisms of apostatic selection, which theorize the survival of individual prey animals whose mutations make them less likely to be attacked by predators. In other words, the more different a prey animal is from others, the less likely it will be targeted by predators. The high abundance prey animals within the Biological Reserve of Tapirapé seems to support this prediction. This report exemplifies the importance of monitoring the biodiversity and promoting the conservation of favorable habitats to support species multiplicity in highly fragmented regions, as in the Brazilian Amazon.